Manajemen Pendidikan Karakter dalam Menumbuhkan Sikap Religius Peserta Didik MI Mafatihul Akhlaq Jepara - Hanik, Elya Umi; Ahsani, Eva Luthfi Fakhru (QUALITY, 2021)
This study aims to analyze the management of character education in growing the religious character of students at MI Mafatihul Akhlaq Jepara. This research is a field research with a qualitative method approach. The object of this research is MI Mafatihul Akhlaq Demangan, Tahunan, Jepara. This research data collection using interview techniques, observation and documentation, technical data analysis through the stages of data collection, data reduction, data presentation and classification and validity test using data triangulation techniques. The results of this study include; 1) the character education management model implanted at MI Mafatihul Akhlaq Jepara includes the process of planning, organizing, implementing and evaluating it, religious character, honesty, intelligence, and caring for others. Teachers have strategies to support the achievement of the concept of character education management. 2) Strategies in implementing character education in fostering the religious attitude of students through example, learning, empowerment and civilizing, strengthening, and assessment.